FORMATION OF TRAINING SYSTEM OF TEACHERS IN SOVIET UKRAINE (1917-1932) (Pedagogy of Higher and Secondary Education, 2007)
In the article the problems of forming of the national system of the teaching personnel training in USRR in 1917-1932 are considered.